Support And Role of Husbands in Post-Mastectomy Patient Care: Literature Review - Tri Sejati Kartika Dewi; Warsiti Warsiti; Yuni Purwati (Borneo Nursing Journal (BNJ), 2026)
Background:Mastectomy for advanced breast cancer not only has physical but also significant psychological consequences for women. Changes in body image, feelings of loss, and limitations in activities often affect the harmony of household life, including the husband. In this situation, the husband plays the role of primary caregiver, providing support for his wife, but also faces stress, uncertainty, and psychological changes due to his wife's condition. Objective:To exploring the husband's experience as a caregiver for his wife in caring for her after a mastectomy.Methode:This literature review research method used databases, namely Pubmed, SINTA, Science Direct, Researchgate, Google Scholar. The keyword were post mastektomi, family support, husband support, body image, Quality of life. Data analysis used literature selection (PRISMA) with inclusion criteria of manuscripts that could be accesed in full text in the range of 2020-2025. Result:The results of the journal analysis show that the majority of studies look at the perspective of cancer survivors, with support from the family in general, not from the husband as the wife's caregiver after a mastectomy. Conclusion and suggestion:Most studies only look at the perspective of cancer survivors, and support is provided only by families in general, with no support from the husband's perspective.